Performance of concrete exposed to freezing and thawing in different saline environments - Šelih, Jana (Journal of Civil Engineering and Management, 2010)
Selection of de‐icing agent applied to the road surfaces can crucially affect the winter driving conditions as well as the deterioration of materials employed in the road structures in cold climates. In particular, concrete as one of the main construction load bearing materials can be affected. Road managers should therefore base their decisions regarding the selection of de‐icing agent not only on data regarding their defrosting potential but also on data related to deterioration rates of materials built in the road infrastructure system. The paper presents the results of a study where the influence of different types of de‐icing salts upon concrete performance was assessed in laboratory conditions. The theoretical background of freezing and thawing in the presence of de‐icing salts in concrete is summarized. Salt scaling tests were performed using 3 selected de‐icing salts on 3 different types of concrete. The mass scaled off the surface was weighed after every 5 freeze‐thaw cycles. The results obtained show that a CaCl2 solution has the most destructive effect upon concrete performance, regardless of the type of concrete. Deterioration was the least when a MgCl2solution was applied to the concrete surface. First Published Online: 24 Jun 2011